MENGHADAPI HEGEMONI PASAR: KOMUNITAS BASIS GEREJAWI SEBAGAI PILAR GERAKAN CIVIL SOCIETY - Jelahu, Timotius Tote (STIPAS TAHASAK DANUM PAMBELUM KEUSKUPAN PALANGKARAYA, 2017)
Abstract:The strengthening of civil society was warmly discussed in Indonesia in the1990s with various actions in response to the New Order. In the discourseand history of the civil society movement, the role of religion is quite strategic.This article explores the development of the Basic Ecclesial Community asa form of civil societies that can contribute to the creation of new habits inthe society. The Basic Ecclesial Community can fortify its members fromeconomic structures that do not take sides to the equality of human dignityand justice. One way that can be taken by the Basic Ecclesial Community isthe strengthening of peopleâs economy through credit union in the middle ofeconomic globalization with the terms of market hegemony